Infusion of Hibiscus sabdariffa L. Modulates Oxidative Stress in Patients with Marfan Syndrome - María Elena Soto; Alejandra Zuñiga-Muñoz; Verónica Guarner Lans; Erendira Janet Duran-Hernández; Israel Pérez-Torres (Hindawi Limited, 2016)
Marfan syndrome (MFS) is associated with progressive aortic dilatation, endothelial dysfunction, and oxidative stress that contribute to the early acute dissection of the vessel and can end up in rupture of the aorta and sudden death. Many studies have described that the organic acids from Hibiscus sabdariffa Linne (HSL) calyces increase cellular antioxidant capacity and decrease oxidative stress. Here we evaluate if the antioxidant properties of HSL infusion improve oxidative stress in MFS patients. Activities of extra cellular super oxide dismutase (ECSOD), glutathione peroxidase (GPx), glutathione-S-transferase (GST), glutathione reductase (GSSG-R), glutathione (GSH), lipid peroxidation (LPO) index, total antioxidant capacity (TAC), and ascorbic acid were determined in plasma from MFS patients. Values before and after 3 months of the treatment with 2% HSL infusion were compared in control and MFS subjects. After treatment, there was a significant decrease in ECSOD (p=0.03), EGPx (p=0.04), GST (p=0.03), GSH (p=0.01), and TAC and ascorbic acid (p=0.02) but GSSG-R activity (p=0.04) and LPO (p=0.02) were increased in MFS patients in comparison to patients receiving the HSL treatment and C subjects. Therefore, the infusion of HSL calyces has antioxidant properties that allow an increase in antioxidant capacity of both the enzymatic and nonenzymatic systems, in the plasma of the MSF patients.